A simplified approach to environmental science - Abdullahi, Hashim; Asmawi, M. Zainora (Pyla-mak Services, 2017)
This book addresses fundamental components associated within the concept of environmental science. It covers the components of ecosystem, environmental hazards,environmental pollution, natural resources, environmental conservation, sustainable development, urban development control as tool for sustainable development, contribution of natural resources, and climate change and its effects in Nigeria. Overall, it is hope that the book can contribute to the body of knowledge of environmental science.